2013
DOI: 10.1259/dmfr.20130071
|View full text |Cite
|
Sign up to set email alerts
|

Carious lesions: diagnostic accuracy using pre-calibrated monitor in various ambient light levels: anin vitrostudy

Abstract: There is no evidence that any difference between ambient light levels affects the ability to detect carious lesions in digital radiographs as long as the monitor was calibrated in accordance with the surrounding light level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 18 publications
3
17
2
Order By: Relevance
“…The interval window length is longer than the more commonly reported two weeks, however it is approximately half that of some other studies which reviewed images after at least six months. 2,17,18 In two studies by Hellén-Halme et al 19,20 they reported intraobserver agreement ranging from fair to moderate, which was similar to our restored molar agreement. 19,20 However our intraobserver agreement was significantly higher than Hellén-Halme et al 19,20 for the primary caries detection on the premolar, which was observed to be from moderate to almost perfect.…”
Section: Chapter 3 Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The interval window length is longer than the more commonly reported two weeks, however it is approximately half that of some other studies which reviewed images after at least six months. 2,17,18 In two studies by Hellén-Halme et al 19,20 they reported intraobserver agreement ranging from fair to moderate, which was similar to our restored molar agreement. 19,20 However our intraobserver agreement was significantly higher than Hellén-Halme et al 19,20 for the primary caries detection on the premolar, which was observed to be from moderate to almost perfect.…”
Section: Chapter 3 Resultssupporting
confidence: 89%
“…2,17,18 In two studies by Hellén-Halme et al 19,20 they reported intraobserver agreement ranging from fair to moderate, which was similar to our restored molar agreement. 19,20 However our intraobserver agreement was significantly higher than Hellén-Halme et al 19,20 for the primary caries detection on the premolar, which was observed to be from moderate to almost perfect. The interobserver agreements were similar to that of Hellén-Halme et al 19,20 in regards to the restored molar; again the premolar had a higher agreement range reaching almost perfect.…”
Section: Chapter 3 Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…25,26 Authors claimed that the ability to detect carious lesions by experienced clinicians can be enhanced by hooding laptop displays in bright clinical environments. 25 In a previous study, 26 seven observers evaluated teeth for proximal carious lesions on standardized intraoral digital radiographs using three setups as follows: (1) precalibrated monitor for high ambient light (.1000 lux), (2) precalibrated monitor for low ambient light (,50 lux) and (3) Barten calibration (digital imaging and communication in medicine) on the monitor in dimmed ambient light (,50 lux). Authors found no difference in diagnostic accuracy for the detection of any type of proximal carious lesions between the different calibration modes of the monitor according to different ambient light levels.…”
Section: Discussionmentioning
confidence: 99%
“…Authors concluded that monitor calibration according to ambient light level eliminates the negative effects of ambient light in detection of carious lesions in digital radiographs. 26 In the present study, ambient light was not an issue, as we assessed all types of images under dimmed light and no calibration was applied to display modes prior to viewing sessions.…”
Section: Discussionmentioning
confidence: 99%